Optimalisasi Kemampuan Anak dalam mencuci Tangan menggunakan Sabun sesuai Metode Cuci Tangan Yang Benar - Yustanta, Brivian Florentis (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2024)
Washing hands with soap is one of the most effective ways to prevent diarrheal disease and ARI, both of which are the main causes of child death. The Indonesian public's awareness of CTPS is still very low, with an average of 12% of people practicing CTPS. The aim is to know the ability of children to wash their hands with soap after a demonstration on how to wash their hands properly at Tri Dharma Kindergarten, Banjaragung Village, Bareng District, Jombang Regency. The type of research used in this research is descriptive quantitative. In this study there was a population of 41 respondents. Researchers used a simple random sampling technique to obtain a sample of 37 respondents. The variable in this study was a single variable, namely the child's ability to wash their hands with soap after demonstrating how to wash their hands properly. While the instrument used is an assessment sheet. This research was conducted on June 23-24 2023 at the Tri Dharma Kindergarten in Banjaragung Village, Bareng District, Jombang Regency. Based on the results of the study that there were 11 children (29.73%) doing hand washing with soap well, 19 children (51.35%) doing hand washing with soap quite well, and 7 children (18.92%) lacking in washing hands with soap. Lack of education, experience and information about washing hands with soap can affect children's behavior. Health education is very important to improve health status. By holding health education in the form of training it is hoped that it can increase knowledge and change children's behavior regarding the implementation of hand washing with soap. It can be concluded that the ability of children to wash their hands with soap after a demonstration of how to wash their hands properly at Tri Dharma Kindergarten, Banjaragung Village, Bareng District, Jombang Regency is categorized as moderate/good enough in its application, seen from the highest percentage, namely 19 respondents (51.4%).